BILINGUALISME PEDAGANG ETNIS TIONGHOA DI PASAR SIBORONGBORONG TAPANULI UTARA - Betti Siburian; Rudiansyah Rudiansyah (Kantor Bahasa Provinsi Maluku Utara, 2021)
Siborongborong Chinese Ethnic Traders are multilingual people who are able to speak Mandarin, Batak Toba, and Indonesian language. This study aims to describe the code switching and codes used by ethnic Chinese traders in Siborongborong market in the realm of trade, as well as factors in the use of language in the realm of commerce in the Siborongborong Chinese community. The research method used is a qualitative-descriptive approach, which examines language in its relation to the community who uses it. This study uses the theory put forward by Kridalaksana, that language as an object in sociolinguistics is not seen or approached as a people's language which is carried out by general linguistics, but as a means of interaction or communication in society. Interview techniques and data analysis were carried out using listening techniques, engaging listening techniques, interviewing techniques and questionnaires. These results explain that there is the use of bilingualism as well as external code switching by ethnic Chinese traders from Siborongborong, namely from the Toba Batak language to Indonesian, as well as from the Toba Batak language to Mandarin. The factors that influence the use of community language in the Siborongborong Chinese ethnic group are due to the ethnic background, the presence of a third speaker, continuous language contact and a familiarity in the situation in the speech.